The BH4 domain of Bcl-2 orthologues from different classes of vertebrates can act as an evolutionary conserved inhibitor of IP3 receptor channels. (March 2017) - Ivanova, Hristina; Luyten, Tomas; Decrock, Elke; Vervliet, Tim; Leybaert, Luc; Parys, Jan B.; Bultynck, Geert
Graphical abstract: Highlights: The BH4 domain of Bcl-2 is conserved among different classes of vertebrates. The Bcl-2-binding site located in the modulatory IP3 R domain too is conserved. All vertebrate BH4 domains can bind the purified modulatory IP3 R domain from mouse. All vertebrate BH4 domains can inhibit the mouse IP3 R but with different potencies. Abstract: Ca 2+ signalling plays an important role in various physiological processes in vertebrates. In mammals, the highly conserved anti-apoptotic B-cell lymphoma-2 (Bcl-2) protein is an important modulator of the inositol 1, 4, 5-trisphosphate receptor (IP3 R), i.e. the main intracellular Ca 2+ - release channel located at the endoplasmic reticulum (ER). The Bcl-2 Homology (BH) 4 domain of Bcl-2 (BH4-Bcl-2) is a critical determinant for inhibiting IP3 Rs, by directly targeting a region in the modulatory domain of the receptor (domain 3). In this paper, we aimed to track the evolutionary history of IP3 R regulation by the BH4 domain of Bcl-2 orthologues from different classes of vertebrates, including Osteichthyes, Amphibia, Reptilia, Aves and Mammalia . The high degree of conservation of the BH4 sequences correlated with the ability of all tested peptides to bind to the domain 3 of mouse IP3 R1 in GST-pull downs and their overall ability to inhibit IP3 -induced Ca 2+ release (IICR) in permeabilized cells. Nevertheless, the BH4 domains differed in their potency to suppress IICR. The peptide derived from X. laevis was the least potent inhibitor. We identified a critical residue in BH4-Bcl-2 from H. sapiens, Thr7, which is replaced by Gly7 in X. laevis . Compared to the wild type X. laevis BH4-Bcl-2, a "humanized" version of the peptide (BH4-Bcl-2 Gly7Thr), displayed increased IP3 R-inhibitory properties. Despite the differences in the inhibitory efficiency, our data indicate that the BH4 domain of Bcl-2 orthologues from different classes of vertebrates can act as a binding partner and inhibitor of IP3 R channels.